Analisis Bahasa Pemrograman Java dengan Bahasa Pemrograman Visual Basic Program Aplikasi Perkalian Matriks - Fajar Shodik; Arnellis Arnellis (UNIVERSITAS NEGERI PADANG, 2021)
The rapid development of Information Technology today brings ease of work in variousfields, such as mathematics. Complex calculations can be completed easily and quickly just by using acalculator. Calculations can also be done using an application program, where the application isdeveloped using a programming language. Of the many programming languages that exist today,including Java and VisualBasic. This research is a basic research where in this study an analysis of the programming language with matrix multiplication problems is carried out.The purpose oft his research is to see which programming language is better based on predetermined criteria. The research methodused is by analyzing the algorithms of the two programming languages with matrix multiplicationproblems based on relevant sources. The results showed that the Visual Basic is better than the Java based on these criteria.